Study of rainfall-induced slope failure - Harianto Rahardjo. (2009)
Rainfall-induced slope failures frequently occur in residual soil slopes in tropical regions. Previous research works indicated that the main cause of slope failure in residual soil slopes is rainfall infiltration. The infiltrating water decreases matric suction in the soil and consequently reduces shear strength of the residual soil slopes. The role of soil types and soil properties on stability of slopes in Singapore during and after rainfall are investigated. Soils for the laboratory models and from real slopes were characterized in this project. Numerical simulations, including: seepage and slope stability analyses were performed. It was observed that the characteristics of variation in factor of safety of the real slopes in the field during and after a rainfall event were controlled by the hydraulic properties of the soil such as soil-water characteristic curves and permeability functions. Hence, it is imperative to characterize unsaturated soil properties properly in order to have correct understanding of rainfall-induced slope failure mechanism.